Transarterial chemoembolization for advanced hepatocellular carcinoma after failure of first-line systemic treatment: a single-center case series - Qingyu Xu; Bin Leng; Ran You; Lingfeng Diao; Chendong Wang; Zeyu Yu; Guowen Yin (Discover Oncology)
Abstract Background & aims To demonstrate the potential benefits of additional transarterial chemoembolization (TACE) for advanced hepatocellular carcinoma (HCC) after the failure of first-line systemic treatment (ST). Methods This retrospective single-center study was conducted between January 2020 and December 2022 on patients with advanced HCC who failed to respond to initial first-line ST. Patients who had previously undergone TACE were excluded. Eligible patients underwent on-demand TACE in addition to ST and were followed until death or until March 2023. The duration of response was recorded. Overall survival (OS) was calculated from the date of failure of first-line ST to the date of death or last follow-up. The primary outcomes were OS and safety, and the secondary outcomes were time to progression (TTP) and objective response rate (ORR). Results In total, 18 patients were included; 8 patients had failed to respond to lenvatinib or sorafenib monotherapy, and 10 had failed to respond to a combination therapy. The most common progression pattern was the development of new intrahepatic lesions. Salvage treatment consisted of 16 triple therapies and 2 dual therapies, including TACE. The median duration of follow-up was 9.5 months. The median OS from the start of second-line treatment was 24 months. The median TTP was 3.5 months. The ORR was 55.6%, and disease control was achieved in 94.4% of patients. Treatment-related adverse events were common but acceptable. Conclusions Patients with advanced HCC who face significant treatment challenges could potentially benefit from the addition of TACE to second-line ST.